HOW DID LANGUAGE PROFESSIONALS STUDY ENGLISH GRAMMAR IN ITALIAN UNIVERSITIES BEFORE 1980? (Italiano LinguaDue, 2018)
The acquisition of practical as well as scientific/metalinguistic knowledge of English grammar has traditionally been one of the key aims of degree courses preparing English language professionals (teachers, translators etc.) in many European countries. To this end, since the first half of the 1900s, dedicated teaching materials, such as the highly successful grammaticographical genre of university grammars of English, have been produced as a result of research efforts shifting from historical investigations into the English language to the study of contemporary English. This paper is an exploratory investigation of the materials used for the learning/teaching of English grammar in Italian universities before the beginning of so-called “mass higher education”. In particular, two English language teaching textbooks written by Italian Anglicists in two decades post WWII have been scrutinized. The results of the analysis shows that English language materials produced in Italy and used in degree courses for English language professionals in the period under consideration lack the textual features that have been associated with the genre of university grammars of English. In spite of the great strides made in the fields of grammaticography and linguistic science between the 1930s and 1950s, the authors cast themselves in the role of applied linguists and view grammar mainly as a ‘practical’ endeavour rather than as a means to foster the acquisition of language awareness and language analysis skills. Come studiavano la grammatica inglese gli studenti di Lingue e Letterature Straniere nelle università italiane prima del 1980?L’acquisizione di una conoscenza a livello pratico e scientifico/metalinguistico della grammatica inglese rappresenta tradizionalmente uno degli scopi principali dei corsi di laurea che preparano ‘professionisti’ della lingua inglese (insegnanti, traduttori ecc.) in molte nazioni europee. A partire dai primi decenni del Ventesimo secolo, in seguito a un reindirizzamento della ricerca da parte di molti studiosi europei di lingua inglese da un ambito storico allo studio dell’inglese contemporaneo, si è avuta una consistente produzione di materiali didattici, tra cui va annoverato il genere grammaticografico delle grammatiche universitarie di lingua inglese. Lo scopo di questo contributo è di condurre un’indagine esplorativa dei materiali utilizzati per l’apprendimento/insegnamento della grammatica inglese nelle università italiane prima dell’avvento della cosiddetta ‘università di massa’. In particolare, si è preso in esame un campione di due testi tratti dalla produzione didattica in lingua inglese di anglisti italiani nei due decenni successivi alla fine del secondo conflitto mondiale. I risultati dell’analisi mostrano che i testi presi in esame non possiedono le caratteristiche di genere che contraddistinguono le grammatiche universitarie di lingua inglese. Malgrado i notevoli passi in avanti compiuti dalla grammaticografia e dagli studi linguistici tra gli anni ’30 e ’50 del secolo scorso, gli autori si presentano nel ruolo di linguisti applicati e concepiscono lo studio grammaticale come finalizzato all’acquisizione di abilità ‘pratiche’ e non allo sviluppo di competenze di riflessione sulla lingua e di analisi linguistica.